PENGARUH TEKNIK RELAKSASI NAFAS DALAM TERHADAP PENURUNAN TINGKAT NYERI PADA PASIEN POST SECTIO CESARIA DI RUANG RAWAT INAP KEBIDANAN RSUD PARIAMAN - Sari Setiarini - (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Sectio cesaria is a method of giving birth to the fetus through an incision in the abdominalwall and uterine wall. The result of Riskesdas 2013 was 9,8% by cesarean section with highestproportion in DKI Jakarta (19,9%) and lowest in Southeast Sulawesi (3,3%) Based on medicalrecord data of RSUD Pariaman, patients who operate in midwifery room 113 people. One ofthe sectio cesarial complications is the painful method of treating non-pharmacological painrelief in deep breath relaxation techniques. The purpose of this study was to determine theeffect of breath relaxation technique on the decrease of pain level in Patient Post SectioCesaria In Inpatient ward of Midwifery RSUD Pariaman.The type of this research is experiment conducted by using quantitative approach withexperimental quasi design with One group Pretest-postest design design. This study wasconducted in the Inpatient ward of Midwifery Pariaman Hospital population was 113 people,with sample 10 because taken by acidental sampling. Data were collected and analyzed usingWilcoxon Test.The result of the research on wilcoxon test shows the mean rank scale of the pretestrespondent's pain scale of 5.50 and the post test of 0.00, with the mean of post-test pain scaledown from pre test. Then there is the effect of deep breath relaxation technique on thedecrease of post sectio cesarial pain level with p value = 0.004 (p <0.005).Researchers suggest to health workers, especially in the Midwifery ward to teach relaxationbreath techniques in patients post sectio cesaria to reduce pain experienced by patients.Keyward : pain level, deep breath, pre and post pest.